Teknologi Pengolahan Tepung Daun Kelor Sebagai Substitusi Bahan Pewarna Alami Terhadap Olahan Pangan - Novi Mailidarni; Aprita, Ika Rezvani; Yanti, Fitri; Rejeki, Sri Untari Puji (Pencerah, 2022)
Moringa (Moriga oleifera Lam) is not only a vegetable but also has benefits and ingredients that are good for the health of the body, Moringa also contains vitamins, minerals, protein and fat. One of the most prominent contents of Moringa is antioxidants, especially the leaves which contain high antioxidants. Based on phytochemical tests, Moringa leaves (Moriga oleifera Lam.) contain tannins, steroids and triterpenoids, flavonoids, saponins, inter-quinones, and alkaloids, all of which are antioxidants. This service is carried out in several stages, the first stage is the preparatory stage with activities to coordinate with the head of SMA Negeri 1 Kuta Baro Aceh Besar Regency regarding the cooperation agreement and place of implementation, preparation of workshop materials and preparing time and activities for implementing the workshop on the theme Processing Technology of Moringa Leaf Flour as a Substitution of Natural Coloring Materials for Food Processing. Community service participation in this case involved 23 teacher participants along with 12 student participants from SMA Negeri 1 Kuta Baro, Aceh Besar Regency as training participants with a total of 35 participants. With this activity, cooperation can be established between SMA Negeri 1 Kuta Baro, Aceh Regency. Based on the results of the dedication that has been done, it is known that the teachers and students of SMA Negeri 1 Kuta Baro Aceh Besar Regency are enthusiastic in participating in community service activities related to the themes presented by the presenters regarding knowledge of technology development and the latest innovations in producing a product. The training provided is training needed by partners such as in the analysis of problems which reveals that current problems are related to processed food snacks using dangerous synthetic chemical dyes.